ROLE OF PRO-INFLAMMATORY CYTOKINE GENE POLYMORPHISMS IN PATIENTS WITH EARLY-ONSET VENOUS THROMBOEMBOLISM - A. P. Polyakova; V. M. Shmeleva; M. N. Blinov; V. E. Soldatenkov; V. D. Kargin; L. P. Papayan; S. I. Kapustin (Медицинская иммунология)
Taking into account interrelations between inflammation and hemostasis, as well as immediate effects of IL-1β, IL-6 and TNFα upon blood coagulation system, one may suggest that their functional variantscould determine thrombosis risks both in arterial and venous circulation. The aim of this study was to assess possible role of allelic IL-1β, IL-6 and TNFα variants in pathogenesis of venous thromboembolism (VTE)in young patients. A retrospective analysis was performed for a group of 180 patients with early-onset VTE, and 150 healthy. In a sub-group with deep-vein thrombosis of lower extremities (DWTLE) complicated bypulmonary artery thromboembolia (PAT), we have revealed increased frequencies of IL-6 –174C homozygotes (30.8% vs 13.0%, p = 0.02) and IL-1β –31Т (61.5% vs 40.9%, p = 0.03), when compared with a subgroup of DWTLE. Among patients with “isolated” PAT a tendency for increased IL-1β –31ТТ ratio was found, as compared with DWTLE (53.8% vs 40.9%, р = 0,3), like as with control group (53.8% vs 40.7%, р = 0,3), These differences, however, were statistically insignificant. These data may suggest certain effects of IL-1β and IL-6 gene polymorphisms upon clinical characteristics of venous thromboembolism, rather than upon general VTE risk among young persons.